Aspek keterbatasan akses informasi penghidupan orang miskin pedesaan - Pawit M Yusup; Engkus Kuswarno; Nuning Kurniasih (Faculty of Social and Political Science, Universitas Airlangga, 2017)
This study aims to assess the meaning of poor from the perspectives of poor people in rural areas, specifically in the context of the limited access to livelihood information. The method used in this research is qualitative phenomenological tradition. Data collected by unstructured interview technique, involving 65 informants whom originated from rural poor in the southern part of West Java. The study conducted during 2014-2016. The results illustrate that the meaning of poor and poverty from the perspective of the poor are: those who do not feel fast enough to get information about their livelihood; who feel that there were no another party that tells information about their livelihood; people who feel that nothing can be done to increase their income; who feel that they have no information and knowledge in entrepreneurship; who feel that no need to put effort in seeking of information about livelihood; a person who feels sad to see people scramble around to get information about a living; persons who are not able to compete in getting information related to livelihood; people who do not have information about other parties who can help them out of poverty; people who feel that there are no books and other sources of information ona better technique of entrepreneurship; people who feel that there was inadequate time to read books and other reading materials about entrepreneurship; and, those who feel that they only have limited experience in finding and using information about livelihoods.